Bilan énergétique de l'huître creuse (Crassostrea gigas) durant la période de forte croissance en mai en Baie de Marennes-Oléron (France) - Soletchnik, Patrick; Heral, Maurice; Razet, Daniel; Bougrier, Serge; Geairon, Philippe (ICES-CIEM CM 1993 / K:40, 1993)
Ecophysiological study was conducted on the japanese oyster (Crassostrea gigas) reared in Marennes-Oléron bay (France), during May 1992. Most of the somatic growth of the oyster occured during that month. The measurements were achieved from a removable laboratory stated in Le Chapus for 3 days at different tide level (coefficient of 49, 57, and 88). The food conditions were monitored through a computer with a continuous record of the turbidity during aIl the tidal cycle. In spite of an important variation between the food conditions in mean seston load, from 13,5 to 54,6 mg/!, the available organic matter ranged from 3 to 4,9 mg/l. The rate of organic matter in the water ranged 22 % to 9 %. The organic selection efficiency was significantly higher for the condition 3 compare to the others conditions. This indicated an improvement in the sorting of the oyster at lower organic content (58 %), compare to 30 % and 42 % for the condition 1 and 2. Furthermore, the best absorption rate of the food condition 2 and 3 (coef. 57 and 88), suggested a difference in food quality, probably associated to resuspension of the organic material from the bottom. So, the scope for growth was significantly different for the three conditions in a ratio of 1, 4 and 10, respectively for the conditions 1, 2 and 3 (coeff. 49, 57 and 88). These values ranged from 50 to 500 joules/h/g for three different days in may 1992. Une étude écophysiologique a été réalisée sur l'huître japonaise (Crassostrea gigas), cultivée en baie de Marennes-Oléron (France), en mai 1992. La croissance tissulaire de l'huître se réalise principalement au cours de ce mois. Les mesures ont été effectuées à partir d'un laboratoire mobile positionné sur le site du Chapus, pendant trois jours, et aux coefficients de marée de 49, 57 et 88. Les conditions alimentaires (1, 2, 3), étaient enregistrées sur micro-ordinateur grâce au suivi en continu de la turbidité durant tout le cycle de marée. Malgré des différences importantes de charges particulaires moyennes entre les ...